If you would like to solve <span>(8r^6s^3 – 9r^5s^4 + 3r^4s^5) – (2r^4s^5 – 5r^3s^6 – 4r^5s^4), you can do this using the following steps:
</span>(8r^6s^3 – 9r^5s^4 + 3r^4s^5) – (2r^4s^5 – 5r^3s^6 – 4r^5s^4) = 8r^6s^3 – 9r^5s^4 + 3r^4s^5 – 2r^4s^5 + 5r^3s^6 + 4r^5s^4 = 8r^6s^3 – 5r^5s^4 + r^4s^5<span> + 5r^3s^6
</span>
The correct result would be 8r^6s^3 – 5r^5s^4 + r^4s^5<span> + 5r^3s^6.</span>
all the coordinates of the original triangle have been multiplied by 1/2
A (-4,-6) x 1/2 = -2,-3
B (-8,2) * 1/2 = -4,1
C (-2,4) *1/2 = -1,2
so the scale factor is 1/2
Answer is B
Answer:
Step-by-step explanation:
7x - 4 = 5x - 10
2x - 4 = -10
2x = -6
x = -3
Answer:
6m^4 / n
Step-by-step explanation:
-12m^12 / 2m^8 n
= 6m^4 / n